Se f (×) =3× - 5 com f (2) + f (-2)
Soluções para a tarefa
Respondido por
4
Olá, boa noite!
É só substituir x pelos seus determinados valores.
![f(x)=3x-5\\\\f(2)=3\cdot2-5\\f(2)=6-5\\f(2)=1\\\\f(-2)=3\cdot(-2)-5\\f(-2)=-6-5\\f(-2)=-11\\\\f(2)+f(-2)=\\1+(-11)=\\1-11=\\-10 f(x)=3x-5\\\\f(2)=3\cdot2-5\\f(2)=6-5\\f(2)=1\\\\f(-2)=3\cdot(-2)-5\\f(-2)=-6-5\\f(-2)=-11\\\\f(2)+f(-2)=\\1+(-11)=\\1-11=\\-10](https://tex.z-dn.net/?f=f%28x%29%3D3x-5%5C%5C%5C%5Cf%282%29%3D3%5Ccdot2-5%5C%5Cf%282%29%3D6-5%5C%5Cf%282%29%3D1%5C%5C%5C%5Cf%28-2%29%3D3%5Ccdot%28-2%29-5%5C%5Cf%28-2%29%3D-6-5%5C%5Cf%28-2%29%3D-11%5C%5C%5C%5Cf%282%29%2Bf%28-2%29%3D%5C%5C1%2B%28-11%29%3D%5C%5C1-11%3D%5C%5C-10)
Espero ter ajudado.
Bons estudos! :)
É só substituir x pelos seus determinados valores.
Espero ter ajudado.
Bons estudos! :)
Perguntas interessantes
Ed. Física,
11 meses atrás
Ed. Física,
11 meses atrás
Português,
11 meses atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás